Design and implementation of an optical burst-switched network testbed. - Sun, Yongmei (IEEE Communications magazine)
Optical burst switching has been receiving increased attention as a promising technology for building the next-generation optical Internet. This article presents the design and discusses the implementation of an overlay mode optical burst-switched network testbed. A flexible "transceiver + forwarding" edge node architecture is proposed to perform both electronic burst assembly/disassembly and optical burst forwarding. It is designed to provide class of service and wavelength selection for locally generated bursts, and transparency to cut-through bursts. The functional modules of the control plane and related key design issues are presented. In particular, we discuss a scheduling mechanism that efficiently combines two different contention resolutions in space and wavelength domains. Experimental results show the effectiveness of this scheme in reducing burst blocking probability. Furthermore, the performance of the network testbed and corresponding methods of improving it are discussed.